ENTREPRENEURSHIP IN THE CORONAVIRUS ERA: HOW HAS THE COVID-19 CRISIS AFFECTED ENTREPRENEURSHIP? - Morched, Salim; Jarboui, Anis (Journal of Business And Entrepreneurship, 2021)
In Wuhan, China, and by the end of 2019 until the first half of 2020, the world experienced the proliferation and destruction of the new coronavirus discovery. Many infections and deaths caused by the virus, the collapse of the health care system, and the economic impact have few modern analogs. Many countries present a reaction to the pandemic; however, it arises when a heated debate ensues over which political system’s democracy versus authoritarianism is best suited to reply to the pandemic. As global efforts to contain the virus continue, this article aims to examine how the COVID-19 crisis has had many effects on the cultural lifestyle and social entrepreneurship of every country in the world. This current lack of integration between crisis management, entrepreneurship, and COVID-19 literature are the main points to be discussed. The summary of this analysis is consistently clear in the current literature through the connection of key notions within emergency management and entrepreneurship. Due to COVID-19, a dramatic effect has reached the global society. In fact, and academically speaking, this survey is among the first to study these consequences at different levels, including the cultural, social, and lifestyle entrepreneurship context. As a result, micro, macro, and meso environmental impacts deriving from the COVID-19 crisis can be better understood in the entrepreneurship literature area. At present, the impact of COVID-19 on entrepreneurship has not been studied. That is why this article tries to provide a broader and more comprehensive framework.